Campus Central CU lecturas de un patrimonio vivo - Mendoza Morfín, Gonzalo (Universidad Nacional Autónoma de México, Facultad de Arquitectura, 2019)
CU central campus. Readings of a living heritage is a collection of 19 booklets that compile the history of the buildings that make up the original campus of the University City of UNAM. On the occasion of the 10 years of the inscription of the central campus in the UNESCO World Heritage list, celebrated in 2017, a team of young architects, thesis students and students of the UNAM was given the task of investigating and delving into the history of these buildings in their more than sixty years of existence. Written from a contemporary view, the compiled essays seek to spread the value of CU in the younger generations and, at the same time, add to the historiographic heritage that addresses the theme of modern Mexican architecture